The effects of hydrothermal processing and germination on Fe speciation and Fe bioaccessibility to human intestinal Caco-2 cells in Tartary buckwheat. (15th May 2016) - Pongrac, Paula; Scheers, Nathalie; Sandberg, Ann-Sofie; Potisek, Mateja; Arčon, Iztok; Kreft, Ivan; Kump, Peter; Vogel-Mikuš, Katarina
Highlights: Proportion of Fe species changed marginally in processed Tartary buckwheat grains. In Tartary buckwheat grains, groats and sprouts Fe was bound to phytate and citrate. Lower concentrations of phytate in sprouts did not increase Fe bioaccessibility. The highest Fe bioaccessibility was seen in grains and the lowest in groats. Abstract: Tartary buckwheat is a gluten-free crop with great potential as a wheat substitute. Iron (Fe) is an important mineral element in staple foods which is required in sufficient bioaccessible quantities. The aim of the study was to investigate how processing of grains into groats (hydrothermal processing to remove the husk) and sprouts (7-day-old seedlings) affected Fe speciation (Fe 2+ or Fe 3+ ), Fe ligand composition and Fe bioaccessibility to human Caco-2 cells. Groats contained the least Fe (23.8 ± 1.65 mg kg −1 ) and the lowest amounts of Fe 2+ (8%). Grains and sprouts had comparable Fe concentrations (78.2 ± 2.65 and 68.9 ± 2.73 mg kg −1 ) and similar proportions of Fe 2+ (15% and 18%). The main ligands for Fe in Tartary buckwheat material were phytate and citrate. Phytate was less abundant in sprouts, which did not correlate with greater Fe bioaccessibility. Iron bioaccessibility was 4.5-fold greater for grains than groats, suggesting that Fe is more bioaccessible in the husk than in the rest of the grain.